Spherical aluminum oxide as well as preparation method and application thereof

By using a specific proportion of phthalidite and thin alumina in combination, spherical alumina is prepared by oil ammonia column sphere method, which solves the problem of inappropriate pore structure of spherical alumina support in the prior art, and achieves improvement of the performance of the catalyst and reduction of preparation cost.

CN119911949APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311420966.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing spherical alumina support has the problem of inappropriate pore structure in low-carbon alkane dehydrogenation catalysts, which leads to a decrease in strength and an increase in the deactivation rate of the catalyst. At the same time, the addition of a pore reamer during the preparation process increases cost and contamination.

Method used

Spherical alumina is prepared by using a specific proportion of phthalidite and thin alumina in combination, and oil ammonia column ball-forming method is used to prepare spherical alumina, and the pore diameters are controlled to be distributed between 6-10nm, 10-20nm and 20-50nm to avoid adding pore reamers.

Benefits of technology

The spherical alumina has a suitable pore structure, which improves the catalytic performance, carbon capacity and service life of the catalyst, while reducing the preparation cost and environmentally friendly treatment cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004521076340000251
    Figure BDA0004521076340000251
  • Figure BDA0004521076340000261
    Figure BDA0004521076340000261
  • Figure BDA0004521076340000262
    Figure BDA0004521076340000262
Patent Text Reader

Abstract

The invention relates to the field of spherical aluminum oxide preparation, and discloses spherical aluminum oxide as well as a preparation method and application thereof. In the spherical aluminum oxide, pores with the pore diameter of 6-10 nm account for 0.5-5% of the total pore volume, pores with the pore diameter of 10-20 nm account for 40-60% of the total pore volume, and pores with the pore diameter of 20-50 nm account for 30-50% of the total pore volume. The spherical alumina has a suitable pore structure, and can significantly improve the catalytic performance of a catalyst as a catalyst carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of spherical alumina preparation, and in particular to spherical alumina and a preparation method and application thereof. Background Art

[0002] Activated alumina has suitable pore distribution, good adsorption, thermal stability, surface acidity and large specific surface area. It is one of the most widely used industrial catalyst carriers. In different industrial applications, the shape and requirements of alumina carriers vary according to the different processes used in the industrial process. For moving bed processes such as dehydrogenation of low-carbon alkanes, the alumina carrier used in its catalyst needs to be prepared into a regular sphere in order to reduce the mechanical wear caused by the continuous transportation and recycling of the catalyst during the industrial production process. Since the 1990s, people have conducted a lot of research on the preparation method of spherical alumina. At present, the more mature methods include rotation sphering, spray granulation sphering and oil column sphering, among which oil column sphering is divided into two methods: hot oil column forming and oil ammonia column forming.

[0003] Oil column molding is the main preparation method for spherical alumina carriers used in moving bed catalysts. Compared with methods such as rotating spheres, it has the characteristics of high sphericity and uniform particle size of the prepared alumina spheres. For oil-ammonia column molding, aluminum hydroxide (pseudo-boehmite or boehmite) is generally used as the raw material, and an appropriate amount of acid is added and fully stirred to obtain an alumina sol, which is then dripped into the oil-ammonia column for molding. The upper layer of the oil-ammonia column is the oil layer, and the lower layer is the ammonia water layer. The main function of the oil layer is to make the dripped alumina sol spherical. The surface tension of the selected oil and sol should be large enough to ensure that the dripped sol droplets have good sphericity; the interfacial tension between the ammonia water layer and the oil layer should be small enough to allow the sol spheres formed in the oil layer to smoothly enter the ammonia water layer without deformation; the aluminum hydroxide sol spheres are solidified in ammonia water and become gel spheres, which are then washed, dried, and calcined to obtain spherical alumina carrier products.

[0004] In the preparation process of moving bed catalysts such as dehydrogenation of low-carbon alkanes, the properties of spherical alumina carriers directly determine the performance of the catalyst. The spherical alumina carrier needs to have a large specific surface area to highly disperse the active metal Pt; secondly, the spherical alumina also needs to have a large pore volume to increase the carbon capacity of the catalyst and reduce the deactivation rate of the catalyst; it needs to have sufficient strength and hydrothermal stability to resist mechanical and thermal shocks during the reaction and regeneration process and extend the service life of the catalyst; in addition, the catalyst also needs to have a suitable stacking density. The appropriate stacking density allows a lower catalyst loading to be obtained while achieving the catalytic reaction effect and process requirements, reducing the total amount of catalyst and the total platinum amount of platinum-containing precious metal catalysts, saving investment costs. In recent years, researchers have found that the pore structure of the spherical alumina carrier, that is, the pore size distribution, also has a significant effect on the performance of the catalyst. A larger pore diameter is conducive to increasing the diffusion rate of reactant and product molecules during the reaction and improving the reaction efficiency, but too large a pore size will lead to a decrease in the strength of the catalyst. In order to maintain a large specific surface area and high strength, a certain proportion of small pores needs to be retained in the spherical alumina. Therefore, in recent years, the preparation of spherical alumina carriers with large specific surface area and suitable pore diameter distribution has attracted more and more attention.

[0005] CN105312091A discloses an alumina carrier and a preparation method thereof, which is prepared by oil column molding, adding a pore-expanding agent and adopting two-stage roasting. The alumina carrier has a diameter of 50 to 130 m 2 / g specific surface area, 0.5-1.0ml / g total pore volume, the pore volume of pores with diameters of 2-10nm in the carrier accounts for 4-15% of the total pore volume, the pore volume of pores with diameters of 10-20nm accounts for 40-60% of the total pore volume, the pore volume of pores with diameters of 20-50nm accounts for 1.0-5.0% of the total pore volume, and the volume of macropores with diameters greater than 50nm but not greater than 10μm accounts for 20-50% of the total pore volume. The low-carbon alkane dehydrogenation catalyst prepared by loading the active component on the carrier has good reaction performance.

[0006] In the above-mentioned spherical alumina carrier, there are many macropores with a pore diameter of micrometer level, which can easily reduce the strength of the spherical carrier and affect the catalytic performance of the obtained low-carbon alkane dehydrogenation catalyst. In addition, in the preparation method of the spherical alumina carrier, the pore structure of the spherical alumina carrier is adjusted by adding a pore expanding agent. The addition of the pore expanding agent will increase the manufacturing cost of the spherical alumina carrier, and a large amount of pollutant gas will be generated in the subsequent roasting process, which will increase the cost of environmental protection treatment. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of existing spherical alumina and provide a spherical alumina and its preparation method and application. The spherical alumina of the present invention has a suitable pore structure and can be used as a catalyst carrier to significantly improve the catalytic performance of the catalyst.

[0008] In order to achieve the above objectives, the first aspect of the present invention provides a spherical alumina, in which pores with a pore diameter of 6-10nm account for 0.5-5% of the total pore volume, pores with a pore diameter of 10-20nm account for 40-60% of the total pore volume, and pores with a pore diameter of 20-50nm account for 30-50% of the total pore volume.

[0009] Preferably, in the spherical alumina, there are no pores with a pore diameter less than 6 nm.

[0010] Preferably, in the spherical alumina, pores with a pore diameter greater than 50 nm account for 3-6% of the total pore volume.

[0011] A second aspect of the present invention provides a method for preparing spherical alumina, the method comprising the following steps:

[0012] (1) peptizing pseudo-boehmite and boehmite to obtain aluminum hydroxide slurry;

[0013] (2) dropping aluminum hydroxide slurry into an oil-ammonia column to form wet aluminum hydroxide pellets, and then drying and calcining the wet aluminum hydroxide pellets;

[0014] Wherein, the grain size of the boehmite meets: D (200) / D (002) =5-80, D (200) / D (020) =10-200, wherein the D (020) , D (200) and D (002) are the grain sizes calculated by the Scherrer formula based on the half-width of the diffraction peaks along the (020) crystal plane, (200) crystal plane and (002) crystal plane in the X-ray diffraction curve of boehmite;

[0015] Among them, in the pseudo-boehmite, D (120) =1-10nm, wherein the D (120) is the crystallite size calculated by the Scherrer formula based on the half-peak width of the diffraction peak along the (120) crystal plane in the X-ray diffraction curve of pseudo-boehmite;

[0016] Wherein, based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 15-45%, and the dry mass content of boehmite is 55-85%.

[0017] Preferably, the particle size of the boehmite is 0.1-460 μm, preferably 0.1-400 μm.

[0018] Preferably, the D of the boehmite 50 It is 40-180 μm, preferably 40-80 μm.

[0019] Preferably, the particle size of the pseudo-boehmite is 0.1-300 μm, preferably 0.5-200 μm.

[0020] Preferably, the D of the pseudo-boehmite 50 10-80 μm, preferably 30-60 μm.

[0021] The third aspect of the present invention provides a use of the spherical alumina described in the first aspect or the spherical alumina prepared by the method described in the second aspect in catalyst preparation.

[0022] Through the above technical solution, the beneficial effects of the present invention include:

[0023] The spherical alumina of the present invention has a suitable pore structure and can be used as a catalyst carrier to significantly improve the catalytic performance of the catalyst, while also increasing the carbon capacity of the catalyst, slowing down the catalyst deactivation rate, and increasing the service life of the catalyst. When the catalyst prepared by using the spherical alumina of the present invention as a carrier is used in the field of low-carbon alkane dehydrogenation, it is beneficial to improve the reaction activity, the selectivity of the low-carbon alkane dehydrogenation process, and the product yield. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The first aspect of the present invention provides a spherical alumina, in which pores with a pore diameter of 6-10 nm account for 0.5-5% of the total pore volume, pores with a pore diameter of 10-20 nm account for 40-60% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 30-50% of the total pore volume.

[0026] It should be noted that, in the spherical alumina of the present invention, the pore diameter endpoint of 10 nm is included in pores with a pore diameter of 10-20 nm, and the pore diameter endpoint of 20 nm is included in pores with a pore diameter of 20-50 nm.

[0027] According to the present invention, preferably, in the spherical alumina, pores with a pore diameter of 6-10 nm account for 2-5% of the total pore volume, pores with a pore diameter of 10-20 nm account for 45-60% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 35-50% of the total pore volume. By adopting this preferred embodiment, the catalytic performance of the catalyst can be further improved by using it as a carrier. When the catalyst prepared by using the spherical alumina of the present invention as a carrier is used in the field of light alkane dehydrogenation, it is beneficial to improve the reaction activity, and it is beneficial to improve the selectivity and product yield of the light alkane dehydrogenation process.

[0028] According to the present invention, preferably, there are no pores with a pore diameter less than 6 nm in the spherical alumina. With this preferred embodiment, the pore diameter of the spherical alumina is controlled at a relatively large level, which is conducive to improving the utilization rate of active metals.

[0029] According to the present invention, preferably, in the spherical alumina, pores with a pore diameter greater than 50 nm account for 3-6% of the total pore volume. With this preferred embodiment, the pore diameter of the spherical alumina is controlled to be mainly distributed in the range of 10-50 nm, which is conducive to ensuring that the spherical alumina carrier has a higher strength while maintaining a higher pore volume.

[0030] The pore size distribution, specific surface area and pore volume of the spherical alumina described in the present invention are measured using the Autosorb-6B fully automatic specific surface area and porosity analyzer of the American Quantachrome Company. Determination method: Before the test, the alumina ball sample is vacuum degassed at 1.33Pa and 300°C for 4 hours, and then isothermally adsorbed and desorbed at a liquid nitrogen temperature of 77.4K (-196°C) using high-purity nitrogen as the adsorption medium, and the isotherm is measured; the specific surface area is calculated using the BET (Brunauer-Emmett-Teller) equation, and the pore volume and pore size distribution are calculated using the BJH equivalent cylinder model from the desorption isotherm.

[0031] According to the present invention, preferably, the sphericity of the spherical alumina is greater than 0.95.

[0032] According to the present invention, preferably, the Q of the spherical alumina 0.95 Greater than 95% by volume, wherein Q 0.95 It is the volume proportion of spherical alumina particles with a sphericity greater than 0.95 in all spherical alumina particles.

[0033] The sphericity of the spherical alumina described in the present invention and the average particle size described below are measured using the CAMSIZER multifunctional particle size analyzer of the German RETSCH company. The ideal sphericity of alumina spheres is 1. Under normal circumstances, the sphericity of alumina spheres is less than 1. Sphericity determination of the spherical alumina described in the present invention: the average value of the sphericity of the particles in a 50mL sample. The proportion (volume) of particles with a sphericity (SPHT) greater than 0.95 in the alumina sphere sample is measured using Q 0.95 express.

[0034] According to the present invention, preferably, the crushing strength of the spherical alumina is 40-70N / grain.

[0035] The crushing strength of the spherical alumina described in the present invention is measured by a DL4 type (produced by Dalian Penghui Technology Development Co., Ltd.) particle strength tester. Determination method: Dry the alumina balls at 120°C for 2 hours, put them in a dryer and cool them to 25°C, and take out 50 ball samples to be tested. Set the relevant measurement parameters of the particle strength tester, place a tested alumina ball sample on the sample table, click the measurement button, and the force rod slowly falls to increase the pressure until the ball sample to be measured is broken, and record the pressure data. Among the pressure data of the 50 balls measured, exclude a maximum value and a minimum value, and take the average value of the other data, which is the crushing strength of the tested ball sample.

[0036] The spherical alumina provided by the present invention has high sphericity and strength, can improve the carbon holding capacity of the catalyst during the reaction process, reduce the breakage rate of the catalyst during the continuous reaction process, reduce the loss of the catalyst, and extend the service life of the catalyst.

[0037] According to the present invention, preferably, the spherical alumina is θ-alumina. This preferred embodiment is applied to the dehydrogenation process of low-carbon alkanes, which is beneficial to improving the conversion rate of low-carbon alkanes and product selectivity.

[0038] The crystal structure of the spherical aluminum oxide of the present invention is measured by X-ray diffraction (XRD).

[0039] According to the present invention, preferably, the specific surface area of ​​the spherical alumina is 90-130m 2 / g.

[0040] According to the present invention, preferably, the pore volume of the spherical alumina is 0.5-0.7 cm 3 / g.

[0041] According to the present invention, preferably, the average particle size of the spherical alumina is 1.4-1.8 mm.

[0042] The spherical alumina of the present invention has a relatively suitable specific surface area, pore volume and average particle size. When the catalyst prepared by using the spherical alumina as a carrier is used in the field of low-carbon alkane dehydrogenation, it is beneficial to improve the low-carbon alkane conversion rate and product selectivity.

[0043] A second aspect of the present invention provides a method for preparing spherical alumina, the method comprising the following steps:

[0044] (1) peptizing pseudo-boehmite and boehmite to obtain aluminum hydroxide slurry;

[0045] (2) dropping aluminum hydroxide slurry into an oil-ammonia column to form wet aluminum hydroxide pellets, and then drying and calcining the wet aluminum hydroxide pellets;

[0046] Wherein, the grain size of the boehmite meets: D (200) / D (002) =5-80, D (200) / D (020) =10-200, wherein the D (020) , D (200) and D (002) are the grain sizes calculated by the Scherrer formula based on the half-width of the diffraction peaks along the (020) crystal plane, (200) crystal plane and (002) crystal plane in the X-ray diffraction curve of boehmite;

[0047] Among them, in the pseudo-boehmite, D (120) =1-10nm, wherein the D (120) is the crystallite size calculated by the Scherrer formula based on the half-peak width of the diffraction peak along the (120) crystal plane in the X-ray diffraction curve of pseudo-boehmite;

[0048] Wherein, based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 15-45%, and the dry mass content of boehmite is 55-85%.

[0049] The preparation method provided by the present invention adopts a specific ratio of pseudo-boehmite with a specific grain size to be combined with boehmite, and then the spherical alumina with a suitable pore structure as described in the first aspect can be obtained by an oil-ammonia column spheronization method, which is used as a catalyst carrier and is conducive to improving the catalytic performance of the catalyst. At the same time, the preparation method of the present invention does not add a pore-enlarging agent, which saves costs and is environmentally friendly.

[0050] In the present invention, the specific definitions of pseudo-boehmite and boehmite are well known to those skilled in the art and will not be described in detail herein.

[0051] According to the present invention, preferably, the grain size of the boehmite meets the following requirements: (200) / D (002) =10-60, D (200) / D (020) = 10-80. The use of boehmite having the above-mentioned strip-shaped structure is more conducive to obtaining the spherical alumina having a suitable pore structure as described in the present invention.

[0052] According to the present invention, preferably, the particle size of the boehmite is 0.1-460 μm, preferably 0.1-400 μm.

[0053] According to the present invention, preferably, the D of the boehmite 50 It is 40-180 μm, preferably 40-80 μm.

[0054] Controlling the macroscopic particle size of boehmite within the above range is beneficial to obtaining the spherical alumina having the pore structure described in the first aspect of the present invention, while increasing the pore volume of the spherical alumina.

[0055] According to the present invention, preferably, in the pseudo-boehmite, D (120) = 2-6nm. The use of the above-mentioned small-grained pseudo-boehmite is conducive to obtaining the spherical alumina having the pore structure described in the first aspect of the present invention, and is also conducive to improving the strength of the spherical alumina.

[0056] According to the present invention, preferably, the particle size of the pseudo-boehmite is 0.1-300 μm, preferably 0.5-200 μm.

[0057] According to the present invention, preferably, the D of the pseudo-boehmite 50 10-80 μm, preferably 30-60 μm.

[0058] Controlling the macroscopic particle size of pseudo-boehmite within the above range is beneficial to obtaining the spherical alumina having the pore structure described in the first aspect of the present invention, and is also beneficial to improving the strength of the spherical alumina.

[0059] The inventors found in the research process that in the catalyst preparation method provided by the present invention, by using a specific ratio of boehmite and pseudo-boehmite with specific microscopic characteristics and macroscopic characteristics, wherein the microscopic characteristics refer to the grain size of boehmite and pseudo-boehmite, and the macroscopic characteristics refer to the particle size distribution of boehmite and pseudo-boehmite, the spherical alumina prepared can have a suitable pore structure, and can be used as a catalyst carrier to significantly improve the catalytic performance of the catalyst. In addition, the spherical alumina prepared by the present invention has a high sphericity and strength, which can improve the carbon holding capacity of the catalyst during the reaction process, reduce the breakage rate of the catalyst in the continuous reaction process, reduce the loss of the catalyst, and extend the service life of the catalyst.

[0060] The present invention has no particular limitation on the sources of the pseudo-boehmite and boehmite, which can be purchased commercially or prepared by conventional methods in the art.

[0061] In the present invention, based on the total dry weight of pseudo-boehmite and boehmite, the dry weight content of pseudo-boehmite is 15-45%, preferably 20-40%, such as 15%, 20%, 25%, 30%, 35%, 40%, 45%, and any value in the range formed by any two of these values; the dry weight content of boehmite is 55-85%, preferably 60-80%, such as 55%, 60%, 65%, 70%, 75%, 80%, 85%, and any value in the range formed by any two of these values. Using pseudo-boehmite and boehmite in a specific ratio is conducive to forming a spherical alumina carrier with the aforementioned special pore structure.

[0062] The present invention has a wide range of acid types for the peptization in step (1), which can be a conventional choice in the art. Preferably, the acid used in the peptization in step (1) is an inorganic acid and / or an organic acid, wherein the inorganic acid is nitric acid and / or hydrochloric acid, and the organic acid is selected from at least one of trichloroacetic acid, formic acid and citric acid.

[0063] According to the present invention, preferably, the ratio of the mass of the acid used for the peptization in step (1) to the total mass of pseudo-boehmite and boehmite on a dry basis is 0.01-0.1, preferably 0.01-0.08.

[0064] According to the present invention, preferably, the acid used for the peptization in step (1) is provided in the form of an acid solution, and the concentration of the acid solution is 0.1-2 mol / L, preferably 0.1-1.5 mol / L.

[0065] The present invention has no particular limitation on the peptization process of step (1), and it can be carried out according to conventional methods in the art. Preferably, the peptization time of step (1) is 0.5-20 hours.

[0066] Preferably, the peptization in step (1) is carried out under stirring.

[0067] The present invention has no particular limitation on the stirring rate, which can be appropriately selected according to the specific situation, so as to ensure uniform mixing. Preferably, the stirring rate is 60-300 rpm.

[0068] Preferably, water is also added during the peptization process in step (1).

[0069] The present invention has no particular limitation on the amount of water used, provided that the solid content of the aluminum hydroxide slurry is within the following range.

[0070] According to the present invention, preferably, the solid content of the aluminum hydroxide slurry obtained in step (1) is 16-28% by weight, preferably 18-22% by weight.

[0071] According to the present invention, preferably, the oil-ammonia column comprises an organic phase and an ammonia aqueous phase, and the ratio of the height of the organic phase to the height of the ammonia aqueous phase is 1:5-200.

[0072] Preferably, the height of the aqueous ammonia phase is 100-300 cm.

[0073] The present invention has no particular limitation on the specific type of the organic phase, which can be selected conventionally in the art. Preferably, the organic phase is C5-C 20 The alkane is preferably at least one selected from gasoline, kerosene, petroleum ether, n-pentane, n-hexane, n-heptane, n-octane, n-decane and undecane.

[0074] According to the present invention, preferably, the concentration of the aqueous ammonia is 6-18% by weight.

[0075] The present invention has no particular limitation on the process of preparing wet aluminum hydroxide pellets, and the process can be carried out in accordance with conventional methods in the art. Preferably, the process of dripping aluminum hydroxide slurry into a pelletizing column to prepare wet aluminum hydroxide pellets in step (1) comprises dripping aluminum hydroxide slurry into an organic phase of a pelletizing column to form pellets, and then entering an ammonia aqueous phase to solidify for 0.2-12 hours to form wet aluminum hydroxide pellets.

[0076] Specifically, the process of dripping aluminum hydroxide slurry into a ball-forming column to form wet aluminum hydroxide balls in step (2) includes: dripping aluminum hydroxide slurry into the upper layer of the oil-ammonia column with a ball dropper, and due to the effect of surface tension, the droplets shrink into a ball shape when passing through the upper organic phase layer, pass through the interface between the oil phase and the ammonia water phase, and enter the ammonia water to gel. The gelled particles are solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 0.2-12 hours to become wet aluminum hydroxide balls (i.e., gel balls in the embodiment), which are collected at the bottom of the oil-ammonia column.

[0077] The present invention has no particular limitation on the drying in step (2), and the drying can be carried out according to the commonly used methods in the art. Preferably, the drying conditions in step (2) include: a temperature of 50-150° C. and a time of 5-24 hours.

[0078] Further preferably, the drying conditions in step (2) include: first drying at 50-80° C. for 2-8 hours, and then drying at 90-150° C. for 6-12 hours.

[0079] According to the present invention, preferably, the calcination conditions in step (2) include: a temperature of 800-1200° C. and a time of 2-10 hours.

[0080] The third aspect of the present invention provides an application of the spherical alumina described in the first aspect or the spherical alumina prepared by the method described in the second aspect in catalyst preparation, preferably in the preparation of a low-carbon alkane dehydrogenation catalyst.

[0081] The spherical alumina provided by the present invention is suitable for being used as a catalyst carrier, and is preferably suitable for being used as a carrier of a low-carbon alkane dehydrogenation catalyst.

[0082] Preferably, the active component of the light alkane dehydrogenation catalyst is selected from at least one of noble metals, Group VIII metals and alkali metals.

[0083] The present invention will be described in detail below through examples.

[0084] In the following examples, the test methods for pore size distribution, specific surface area, pore volume, sphericity, crushing strength, and average particle size of spherical alumina were performed according to the test methods given above;

[0085] Grain size test method of boehmite and pseudo-boehmite: XRD diffraction curve was measured by Philips X'pert X-ray diffractometer, using Cu target, Kα radiation, Ni filter, λ=0.154056nm. Solid detector, tube voltage 40kV, tube current 40mA, scanning range 5°-90°. According to Scherrer formula: D=Kλ / (Bcosθ) (D is grain size, λ is the diffraction wavelength of target material, B is the half-peak width of the corrected diffraction peak, 2θ is the position of the diffraction peak);

[0086] The particle size distribution of pseudo-boehmite and boehmite was measured using BetterSize2000 laser scattering instrument from Dandong Better Technology Co., Ltd. The measurement method is as follows: set the particle refractive index: 1.530; particle absorption rate: 0.1; dispersant: water; dispersant refractive index: 1.330; instrument range: 20nm-2mm. Click on automatic calibration, and after the instrument is calibrated, add the sample to be tested into the sample slot. When the concentration reaches the measurement requirement, stop adding, and the instrument will automatically detect. After the detection is completed, record the measured particle size distribution and D 50 value.

[0087] Example 1

[0088] (1) Preparation of pseudo-boehmite and boehmite

[0089] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0090] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 45 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0091] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 12g of 2-hydroxypropionic acid (lactic acid) and 8g of formic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 6h at 120°C and a stirring rate of 200rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0092] (2) Preparation of aluminum hydroxide sol

[0093] Take 30g (alumina dry basis mass) of pseudo-boehmite powder and 70g (alumina dry basis mass) of boehmite powder prepared above, add 273ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 408g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0094] (3) Preparation of alumina balls

[0095] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 1 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1150°C for 3 hours to obtain θ-Al2O3 beads A, with a ball yield of 97.5% by weight.

[0096] The pore diameter distribution of θ-Al2O3 ball A is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0097] Example 2

[0098] (1) Preparation of pseudo-boehmite and boehmite

[0099] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0100] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 45 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0101] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 12g of 2-hydroxypropionic acid (lactic acid) and 8g of formic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 6h at 120°C and a stirring rate of 200rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0102] (2) Preparation of aluminum hydroxide sol

[0103] Take 20g (alumina dry basis mass) of pseudo-boehmite powder and 80g (alumina dry basis mass) of boehmite powder prepared above, add 274ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 410.5g, disperse and peptize for 6 hours at a stirring rate of 100r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0104] (3) Preparation of alumina balls

[0105] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 3 cm high n-octane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1150°C for 3 hours to obtain θ-Al2O3 beads B, with a ball yield of 97.1% by weight.

[0106] The pore diameter distribution of θ-Al2O3 ball B is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0107] Example 3

[0108] (1) Preparation of pseudo-boehmite and boehmite

[0109] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0110] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 45 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0111] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 8 g of 2-hydroxypropionic acid (lactic acid) and 6 g of formic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 10 h at 120° C. and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120° C. for 12 h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0112] (2) Preparation of aluminum hydroxide sol

[0113] Take 35g (alumina dry basis mass) of pseudo-boehmite powder and 65g (alumina dry basis mass) of boehmite powder prepared above, add 271ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 405.5g, disperse and peptize for 1 hour at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0114] (3) Preparation of alumina balls

[0115] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 1 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1150°C for 3 hours to obtain θ-Al2O3 beads C, with a ball yield of 97.3% by weight.

[0116] The pore diameter distribution of θ-Al2O3 ball C is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0117] Example 4

[0118] (1) Preparation of pseudo-boehmite and boehmite

[0119] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0120] The mixture of n-hexyl aluminum and n-hexanol was cooled to 95°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 180 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 200°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0121] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 8 g of 2-hydroxypropionic acid and 6 g of formic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 10 h at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0122] (2) Preparation of aluminum hydroxide sol

[0123] Take 25g (alumina dry basis mass) of pseudo-boehmite powder and 75g (alumina dry basis mass) of boehmite powder prepared above, add 273.5ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 409.3g, disperse and peptize for 2 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0124] (3) Preparation of alumina balls

[0125] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 1 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1150°C for 3 hours to obtain θ-Al2O3 beads D, with a ball yield of 97.5% by weight.

[0126] The pore diameter distribution of θ-Al2O3 ball D is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0127] Example 5

[0128] (1) Preparation of pseudo-boehmite and boehmite

[0129] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0130] The mixture of n-hexyl aluminum and n-hexanol was cooled to 95°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 180 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 200°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0131] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 6 g of 2-hydroxypropionic acid and 4 g of formic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 12 hours at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 hours, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0132] (2) Preparation of aluminum hydroxide sol

[0133] Take 35g (alumina dry basis mass) of pseudo-boehmite powder and 65g (alumina dry basis mass) of boehmite powder prepared above, add 272ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 406.8g, disperse and peptize for 2 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0134] (3) Preparation of alumina balls

[0135] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 5 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1150°C for 3 hours to obtain θ-Al2O3 beads E, with a ball yield of 97.7% by weight.

[0136] The pore diameter distribution of θ-Al2O3 sphere E is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0137] Example 6

[0138] (1) Preparation of pseudo-boehmite and boehmite

[0139] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0140] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 45 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0141] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 20.5 g of citric acid and 13.7 g of acetic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 6 hours at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 hours, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0142] (2) Preparation of aluminum hydroxide sol

[0143] Take 30g (alumina dry basis mass) of pseudo-boehmite powder and 70g (alumina dry basis mass) of boehmite powder prepared above, add 275ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 410.8g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0144] (3) Preparation of alumina balls

[0145] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 6 cm high n-decane and the lower ammonia water phase is 300 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1100°C for 3 hours to obtain θ-Al2O3 beads F, with a ball yield of 96.7% by weight.

[0146] The pore diameter distribution of θ-Al2O3 pellet F is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0147] Example 7

[0148] (1) Preparation of pseudo-boehmite and boehmite

[0149] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0150] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 45 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0151] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 13.7 g of citric acid and 9.1 g of acetic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 10 h at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0152] (2) Preparation of aluminum hydroxide sol

[0153] Take 35g (alumina dry basis mass) of pseudo-boehmite powder and 65g (alumina dry basis mass) of boehmite powder prepared above, add 274ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 409.4g, disperse and peptize for 3 hours at a stirring rate of 200r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0154] (3) Preparation of alumina balls

[0155] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 5 cm high n-decane and the lower ammonia water phase is 200 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1100°C for 3 hours to obtain θ-Al2O3 beads G, with a ball yield of 97.3% by weight.

[0156] The pore diameter distribution of θ-Al2O3 ball G is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0157] Example 8

[0158] (1) Preparation of pseudo-boehmite and boehmite

[0159] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0160] The mixture of n-hexyl aluminum and n-hexanol was cooled to 95°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 180 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 200°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0161] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 13.7 g of citric acid and 9.1 g of acetic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 12 hours at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 hours, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0162] (2) Preparation of aluminum hydroxide sol

[0163] Take 20g (alumina dry basis mass) of pseudo-boehmite powder and 80g (alumina dry basis mass) of boehmite powder prepared above, add 270ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 403.4g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0164] (3) Preparation of alumina balls

[0165] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 3 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1100°C for 3 hours to obtain θ-Al2O3 beads H, with a ball yield of 96.8% by weight.

[0166] The pore diameter distribution of θ-Al2O3 ball H is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0167] Example 9

[0168] (1) Preparation of pseudo-boehmite and boehmite

[0169] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0170] The mixture of n-hexyl aluminum and n-hexanol was cooled to 95°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 180 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 200°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0171] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 10.3 g of citric acid and 6.8 g of acetic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 6 hours at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 hours, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0172] (2) Preparation of aluminum hydroxide sol

[0173] Take 35g (alumina dry basis mass) of pseudo-boehmite powder and 65g (alumina dry basis mass) of boehmite powder prepared above, add 273ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 407.9g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0174] (3) Preparation of alumina balls

[0175] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 2 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1100°C for 3 hours to obtain θ-Al2O3 beads I, with a ball yield of 98.8% by weight.

[0176] The pore diameter distribution of θ-Al2O3 pellet I is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0177] Example 10

[0178] (1) Preparation of pseudo-boehmite and boehmite

[0179] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.

[0180] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 45 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder, and its characteristic parameters are shown in Table 1.

[0181] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 10.3 g of citric acid and 6.8 g of acetic acid was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 6 hours at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 hours, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.

[0182] (2) Preparation of aluminum hydroxide sol

[0183] Take 25g (alumina dry basis mass) of pseudo-boehmite powder and 75g (alumina dry basis mass) of boehmite powder prepared above, add 275.5ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 412.2g, disperse and peptize for 4 hours at a stirring rate of 200r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.

[0184] (3) Preparation of alumina balls

[0185] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 1 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 1100°C for 3 hours to obtain θ-Al2O3 beads J, with a ball yield of 97.6% by weight.

[0186] The pore diameter distribution of θ-Al2O3 ball J is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0187] Comparative Example 1

[0188] The method of Example 1 was followed, except that no boehmite was added during the preparation of the aluminum hydroxide sol, but only pseudo-boehmite was added, specifically: 100 g (alumina dry basis mass) of pseudo-boehmite was added to 261 ml of 0.19 mol / L nitric acid solution for peptization, and then deionized water was added to a total mass of 390.5 g to obtain an aluminum hydroxide sol with a solid content of 20 wt%. Finally, θ-Al2O3 pellets K were obtained, and the pellet yield was 98.9 wt%.

[0189] The pore diameter distribution of θ-Al2O3 ball K is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0190] Comparative Example 2

[0191] The method of Example 1 was followed, except that in the preparation of aluminum hydroxide sol, the mass of pseudo-boehmite was 10 g (alumina dry basis mass), the mass of boehmite was 90 g (alumina dry basis mass), 278 ml of 0.19 mol / L nitric acid solution was added for peptization, and then deionized water was added to a total mass of 416.6 g to obtain an aluminum hydroxide sol with a solid content of 20 wt%. Finally, θ-Al2O3 spheres L were obtained, and the sphere yield was 94.3 wt%.

[0192] The pore diameter distribution of θ-Al2O3 ball L is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0193] Comparative Example 3

[0194] The method of Example 1 was followed, except that no pseudo-boehmite was added during the preparation of the aluminum hydroxide sol, and only boehmite was added, specifically: 100 g (alumina dry basis mass) of boehmite was added to 280 ml of 0.19 mol / L nitric acid solution for peptization, and then deionized water was added to a total mass of 419.5 g to obtain an aluminum hydroxide sol with a solid content of 20 wt%. Finally, θ-Al2O3 pellets M were obtained, and the pellet yield was 87.6 wt%.

[0195] The pore diameter distribution of θ-Al2O3 spheres M is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0196] Comparative Example 4

[0197] The method of Example 1 is followed, except that no grain structure regulator is added to the aluminum hydroxide slurry during the preparation of boehmite. After stirring evenly, the aluminum hydroxide slurry is transferred to a stainless steel autoclave and aged at 120°C for 12 h without stirring. After aging, the slurry is washed with deionized water, then dried in an oven at 120°C for 12 h, and then ground to obtain boehmite powder.

[0198] Finally, θ-Al2O3 pellets N were obtained, and the pellet yield was 94.6% by weight.

[0199] The pore diameter distribution of θ-Al2O3 pellets N is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.

[0200] Table 1

[0201]

[0202]

[0203] Table 2

[0204]

[0205] It can be seen from Table 2 that compared with the comparative example, more than 90% of the pore diameters of the θ-Al2O3 spheres provided by the embodiment of the present invention are uniformly distributed in the range of 10-50 nm, and the volume fraction of pores with a diameter of 10-20 nm is slightly higher than the volume fraction of pores with a diameter of 20-50 nm.

[0206] Table 3

[0207]

[0208]

[0209] It can be seen from Table 3 that the θ-Al2O3 pellets provided by the present invention have good sphericity and high sphericity, which can make the low-carbon alkane dehydrogenation catalyst prepared with the spherical alumina as a carrier less prone to breakage during use, reduce the attrition rate, and extend the operating cycle of the catalyst.

[0210] Test Example 1

[0211] Take 50g (based on dry alumina) of the θ-Al2O3 beads (A, C, H, KN) obtained in the examples and comparative examples as carriers, and take 90g of a solution containing chloroplatinic acid, SnCl2 and hydrochloric acid as an impregnation solution, wherein the impregnation solution contains 0.3 wt% Pt, 0.32 wt% Sn and 1 wt% chlorine (all relative to the dry basis weight of the alumina carrier). The θ-Al2O3 beads A are impregnated with the impregnation solution at 25°C for a total of 4 hours, and the impregnated sample is dried at 120°C for 12 hours and calcined at 500°C for 4 hours. The calcined product is impregnated with 70g of a potassium nitrate solution containing 1 wt% potassium (relative to the dry basis weight of the alumina carrier) at 25°C for 4 hours, and the impregnated solid is dried at 120°C for 12 hours and calcined at 600°C for 4 hours to obtain an oxidized catalyst. The oxidized catalyst is reduced with hydrogen at 550°C for 2 hours to obtain a low-carbon alkane dehydrogenation catalyst. The catalyst contained 0.3 wt% of Pt, 0.32 wt% of Sn, 1 wt% of K and 1 wt% of Cl based on dry alumina.

[0212] In the microreactor, 6 ml of catalyst was loaded, and a mixture of hydrogen and propane was used as the raw material. The purity of propane was greater than 99.9%. At 620°C, 0.21 MPa (absolute pressure), the mass space velocity of propane feed was 3.5 h -1 The reaction was carried out under the condition of a hydrogen / propane molar ratio of 0.5:1, and samples were taken every 1 hour for chromatographic analysis. The propane conversion and propylene selectivity of each catalyst at different reaction times are shown in Table 4.

[0213] Table 4

[0214]

[0215] It can be seen from Table 4 that, compared with Comparative Examples 1-4, the catalyst prepared using the spherical alumina provided in the embodiment of the present invention as a carrier is applied to the propane hydrogen production reaction, and has a higher propane conversion rate and propylene selectivity, and the amount of carbon deposits is reduced, and has good reaction performance.

[0216] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A spherical alumina, characterized in that: In the spherical alumina, pores with a pore diameter of 6-10 nm account for 0.5-5% of the total pore volume, pores with a pore diameter of 10-20 nm account for 40-60% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 30-50% of the total pore volume.

2. The spherical alumina according to claim 1, wherein: In the spherical alumina, pores with a pore diameter of 6-10 nm account for 2-5% of the total pore volume, pores with a pore diameter of 10-20 nm account for 45-60% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 35-50% of the total pore volume; Preferably, there are no pores with a pore diameter less than 6 nm in the spherical alumina; Preferably, in the spherical alumina, pores with a pore diameter greater than 50 nm account for 3-6% of the total pore volume.

3. The spherical alumina according to claim 1, wherein: The sphericity of the spherical alumina is greater than 0.95; Preferably, the Q of the spherical alumina is 0.95 Greater than 95% by volume, wherein Q 0.95 is the volume proportion of spherical alumina particles with a sphericity greater than 0.95 in all spherical alumina particles; Preferably, the crushing strength of the spherical alumina is 40-70N / grain.

4. The spherical alumina according to any one of claims 1 to 3, wherein: The spherical alumina is θ-alumina; Preferably, the specific surface area of ​​the spherical alumina is 90-130m 2 / g; Preferably, the pore volume of the spherical alumina is 0.5-0.7 cm 3 / g; Preferably, the average particle size of the spherical alumina is 1.4-1.8 mm.

5. A method for preparing spherical alumina, the method comprising the following steps: (1) peptizing pseudo-boehmite and boehmite to obtain aluminum hydroxide slurry; (2) dropping aluminum hydroxide slurry into an oil-ammonia column to form wet aluminum hydroxide pellets, and then drying and calcining the wet aluminum hydroxide pellets; Wherein, the grain size of the boehmite meets: D (200) / D (002) =5-80, D (200) / D (020) =10-200, wherein the D (020) , D (200) and D (002) are the crystallite sizes calculated by the Scherrer formula based on the half-peak widths of the diffraction peaks along the (020) crystal plane, (200) crystal plane and (002) crystal plane in the X-ray diffraction curve of boehmite; Among them, in the pseudo-boehmite, D (120) =1-10nm, wherein the D (120) is the crystallite size calculated by the Scherrer formula based on the half-peak width of the diffraction peak along the (120) crystal plane in the X-ray diffraction curve of pseudo-boehmite; Wherein, based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 15-45%, and the dry mass content of boehmite is 55-85%.

6. The method according to claim 5, wherein: The grain size of the boehmite meets the following requirements: D (200) / D (002) =10-60, D (200) / D (020) =10-80; Preferably, the particle size of the boehmite is 0.1-460 μm, preferably 0.1-400 μm; Preferably, the D of the boehmite 50 It is 40-180 μm, preferably 40-80 μm.

7. The method according to claim 5, wherein: In the pseudo-boehmite, D (120) =2-6nm; Preferably, the particle size of the pseudo-boehmite is 0.1-300 μm, preferably 0.5-200 μm; Preferably, the D of the pseudo-boehmite 50 10-80 μm, preferably 30-60 μm.

8. The method according to any one of claims 5 to 7, wherein: Based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 20-40%, and the dry mass content of boehmite is 60-80%; Preferably, the acid used for the peptization in step (1) is an inorganic acid and / or an organic acid, the inorganic acid is nitric acid and / or hydrochloric acid, and the organic acid is at least one selected from trichloroacetic acid, formic acid and citric acid; Preferably, the mass ratio of the acid used for peptization in step (1) to the pseudo-boehmite on a dry basis is 0.01-0.1; Preferably, the acid used for the peptization in step (1) is provided in the form of an acid solution, and the concentration of the acid solution is 0.1-2 mol / L; Preferably, the aluminum hydroxide slurry obtained in step (1) has a solid content of 16-28% by weight.

9. The method according to any one of claims 5 to 8, wherein: The oil-ammonia column includes an organic phase and an ammonia aqueous phase, and the ratio of the height of the organic phase to the height of the ammonia aqueous phase is 1:5-200; Preferably, the organic phase is C5-C 20 Alkanes, preferably at least one selected from gasoline, kerosene, petroleum ether, n-pentane, n-hexane, n-heptane, n-octane and undecane; Preferably, the concentration of the aqueous ammonia is 6-18% by weight.

10. The method according to any one of claims 5 to 9, wherein: The calcination conditions in step (2) include: a temperature of 800-1200° C. and a calcination time of 2-10 hours.

11. Use of the spherical alumina according to any one of claims 1 to 4 or the spherical alumina prepared by the method according to any one of claims 5 to 10 in catalyst preparation, preferably in low-carbon alkane dehydrogenation catalyst.

Citation Information

Patent Citations

  • Alumina carrier and preparation method thereof

    CN105312091A